Global Plant Health Assessment: Impact of plant health on the ecosystem services rendered by plant systems in world's ecoregions - Singh, Manjari (2023)
This presentation is the second talk of the keynote session K4 "Global Plant Health Assessment (GPHA)". The overall results pertaining to the assessment of the impact of disease on ecosystem services (provisioning, regulating, and cultural) and its evolution over the last 10 years has been outlined. Specific results for a limited number of Plant Systems (rice, potato, peri‐urban horticulture and household gardens, softwood forests, and oak forests) has been described in more detail, allowing to highlight key findings of the results. These include: the paucity of hard data on crop losses caused by plant pathogens worldwide; the impact of plant diseases on food security; pathogen invasions threatening food security and biodiversity; climate change impacts on crops and crop losses; the challenges of pesticide misuse; and the conservation of plant species that are endangered by diseases, especially in the case of forest species.